A Literature review of Routing and Cloud Deployment Methodologies used in an Air Vehicle - Balasubramaniam, Vivekanadam (Journal of Artificial Intelligence and Capsule Networks, 2021)
We present a complete overview of routing protocols, routing algorithms, path planning, and cloud deployment for vehicle navigation in several fields of study in this article. In this article, we compare several approaches and algorithms with the goal of identifying the best feasible ones based on the type of application being utilized. In general, navigation of vehicles will be based on models and methods. Hence in this paper each characteristics are examined in detail and the research has been done accordingly. Under each characteristic, performance evaluation criteria are separately analysed. Questions are also provided for which the literature review serves as a form of discussion, according to the research challenge and criteria. For path planning, node-based as well as traditional algorithms are considered as the best choices. Similarly, the performance is significantly improved when using hybrid routing protocols and route planning methodologies that prefer graph based techniques. It has been observed that, a number of future research directions such as routing algorithm with queuing theory and path planning with critical link methods also serve the probable domains. This work is a concise comprehensive study of the various characteristics of a vehicle with respect to navigation. A comparison of techniques, algorithms and methods by using the standard performance criteria has also been elaborated.